Intersecting Mental Health and Sexual and Reproductive Health - Timilsina, Amit (Health Prospect, 2018)
Mental Health and Sexual and Reproductive Health are well-studied with accolades of literature on each topic; however, their interrelationships have been under-described. Mental Health problems can be result of concurrent or past Sexual and Reproductive Health ill event and vice versa. This article presents intersection between Mental Health and Sexual and Reproductive Health based on available literature. Intersections between Mental Health and Sexual and Reproductive Health and their impacts can be studied through life course perspective and needs prioritized attention in case of Gender Based Violence and for people living with disability. The article highlights the importance to explore other aspects such as emotions, gender and sexuality associated with Mental Health and to study and understand physiological and psychological context between Mental Health and Sexual and Reproductive Health. It also stresses the need of further research on intersection between Mental Health and Sexual and Reproductive Health.